Progranulin Protects Against Airway Remodeling Through the Modulation of Autophagy via HMGB1 Suppression in House Dust Mite-Induced Chronic Asthma - Liu M; Shan M; Zhang Y; Guo Z (Dove Medical Press, 2021)
Meixuan Liu,1,2 Mengtian Shan,1 Yunxuan Zhang,3 Zhongliang Guo1,2 1Department of Respiratory Medicine, Shanghai East Hospital, School of Medicine, Tongji University, Shanghai, 200123, People's Republic of China; 2Department of Respiratory Medicine, Shanghai East Clinical Medical College, Nanjing Medical University, Shanghai, 200123, People's Republic of China; 3Department of Pharmacy, Huadong Hospital, Fudan University, Shanghai, 200040, People's Republic of ChinaCorrespondence: Zhongliang Guo Tel +86 18901681968Email drguozhl@163.comPurpose: Airway remodeling is an important feature of chronic asthma, and yet there are few effective therapeutic strategies. Progranulin (PGRN) has been shown to have lung protective functions, but the role of PGRN in asthmatic airway remodeling is unclear. We aim to explore the protective potential of PGRN on house dust mite (HDM)-induced airway remodeling and the underlying mechanisms.Methods: In this study, a murine model of chronic asthma was established by HDM sensitization and challenge. Recombinant PGRN was intranasally administrated to mice during the phase of HDM challenge. TGF-β 1-treated human airway epithelial BEAS-2B cells were utilized to explore the effect of PGRN on airway epithelia exposed to profibrotic conditions and molecular mechanisms.Results: We found that PGRN treatment attenuated HDM-induced airway remodeling, as evidenced by the suppression of collagen accumulation, mucus overproduction and airway smooth muscle synthesis in HDM-challenged asthmatic mice lungs. Meanwhile, PGRN also reversed the increased levels of autophagy markers and autophagosomes in airway epithelia under mimic asthmatic conditions, thereby controlling the fibrotic process in vivo and in vitro. Specifically, overexpressed HMGB1 and the subsequent RAGE/MAPKs signaling activation due to HDM exposure were abrogated in PGRN-treated asthmatic mice. Furthermore, knockdown of HMGB1 expression significantly restrained the fibrosis formation in TGF-β 1-induced airway epithelia accompanied by the downregulation of autophagic activity. However, enhancement of extracellular HMGB1 levels blunted the inhibition of autophagic flux by PGRN in airway epithelia, thereby resulting in the augmentation of collagen synthesis and fibrosis.Conclusion: Taken together, our data revealed that PGRN protected against asthmatic airway remodeling by negatively regulating autophagy via HMGB1 suppression, which might provide new insights into the therapeutic options for HDM-induced chronic asthma.Keywords: house dust mite-induced asthma, airway remodeling, progranulin, autophagy, HMGB1